2017
DOI: 10.1111/febs.14358
|View full text |Cite
|
Sign up to set email alerts
|

ER stress in skeletal muscle remodeling and myopathies

Abstract: Skeletal muscle is a highly plastic tissue in the human body that undergoes extensive adaptation in response to environmental cues, such as physical activity, metabolic perturbation, and disease conditions. The endoplasmic reticulum (ER) plays a pivotal role in protein folding and calcium homeostasis in many mammalian cell types, including skeletal muscle. However, overload of misfolded or unfolded proteins in the ER lumen cause stress, which results in the activation of a signaling network called the unfolded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
157
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 172 publications
(261 reference statements)
4
157
0
1
Order By: Relevance
“…ERp44 is a pH‐regulated chaperone of the secretory pathway, which controls oxidative‐related protein misfolding in the ER . These results are in accordance with studies showing that ER stress is activated in several catabolic situations (denervation, starvation, high‐fat diet, cancer cachexia, and ageing) . The ER stress response can be activated by several stress factors (nutrient deprivation, reactive oxygen species, etc.)…”
Section: Discussionsupporting
confidence: 85%
“…ERp44 is a pH‐regulated chaperone of the secretory pathway, which controls oxidative‐related protein misfolding in the ER . These results are in accordance with studies showing that ER stress is activated in several catabolic situations (denervation, starvation, high‐fat diet, cancer cachexia, and ageing) . The ER stress response can be activated by several stress factors (nutrient deprivation, reactive oxygen species, etc.)…”
Section: Discussionsupporting
confidence: 85%
“…Because of the critical role played by the ER in many aspects of cellular function, it is perhaps unsurprising that dysfunction of the UPR proved to be a factor in the pathogenesis of many human diseases . Almost no tissues are spared from ER stress‐related damage and in this Special Issue of The FEBS Journal , the roles of ER stress in diseases affecting the lung, liver, skin, muscle and nervous system are each examined in detail .…”
mentioning
confidence: 97%
“…Dil Afroze and Ashok Kumar review the recent literature implicating ER stress in the biology of muscle . A tissue often overlooked in the study of ER stress, skeletal muscle has a highly specialized ER (the sarcoplasmic reticulum) that is central to excitation contraction coupling.…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that the abundance and activity of various components of the UPR are increased in skeletal muscle of rodents and humans in multiple conditions of muscle growth and atrophy (5,10). For example, the expression of various ER stress and UPR markers is increased in skeletal muscle in response to both endurance and acute exercise (5,11). It has been reported that the cleaved form of ATF6a interacts with peroxisome proliferator-activated receptor-g coactivator-1a to induce an adaptive UPR in skeletal muscle after acute exercise (12).…”
mentioning
confidence: 99%
“…It has been reported that the cleaved form of ATF6a interacts with peroxisome proliferator-activated receptor-g coactivator-1a to induce an adaptive UPR in skeletal muscle after acute exercise (12). Moreover, markers of ER stress and the UPR have been found to be elevated in skeletal muscle undergoing atrophy (11,13,14). For example, levels of CCAAT/ enhancer-binding protein (C/EBP) homologous protein (CHOP), a downstream target of the PERK arm of the UPR, are increased in skeletal muscle of mice upon denervation.…”
mentioning
confidence: 99%